Design, synthesis, and antimicrobial screening of novel pyridyl-2-amidrazone incorporated isatin mannich bases - N Saravana Kumar; T Pradeep; G Jani; Divya Silpa; B Vijaya Kumar (Wolters Kluwer Medknow Publications, 2012)
Isatin is an endogenous compound and reported to possess a wide range of biological activities. Numerous papers have shown that the pyridyl-2-amidrazone nucleus possesses a potent antimicrobial activity . Based on these prior observations, we postulated that a compound containing both isatin and pyridyl-2-amidrazone pharmacophores could be very effective for antimicrobial activity. Unfavorable adsorption, distribution, metabolism, and excretion (ADME) properties can in many cases lead to the clinical trials failure of potentially successful drug candidates. Their evaluation, therefore, at an earlier stage is desired. Here, we also present the predicted ADME properties of our ligands through computation. All the compounds (2a1 - 5 ) exhibited a better solubility, diffusion, Log P, molecular weight, etc., with no violations making the ligands pharmacodynamically active and better oral absorptive series. Based on the results of computational design, a series of novel pyridyl-2-amidrazone-incorporated isatin Mannich bases were synthesized and screened for their antimicrobial activities. IR, 1 H-NMR, and Mass Spectroscopy data were consistent with the assigned structures. The results exhibited that all of the lead compounds showed good antimicrobial activities; noticeably, the compound 2a 2 showed the best activity against Candida albicans (16 μ g/ml) and compound 2a 3 was found to be the most active derivative against Staphylococcus aureus and Escherichia coli at minimal inhibitory concentration values of 4 and 32 μ g/ml, respectively.